Perspectives in Immunotherapy: meeting report from the Immunotherapy Bridge, December 1st–2nd, 2021 - Paolo A. Ascierto; Antonio Avallone; Nina Bhardwaj; Carlo Bifulco; Sergio Bracarda; Joshua D. Brody; Luigi Buonaguro; Sandra Demaria; Leisha A. Emens; Robert L. Ferris; Jérôme Galon; Samir N. Khleif; et al. (Journal of Translational Medicine, 2022)
Abstract Over the past decade, immunotherapy has become an increasingly fundamental modality in the treatment of cancer. The positive impact of immune checkpoint inhibition, especially anti-programmed death (PD)-1/PD-ligand (L)1 blockade, in patients with different cancers has focused attention on the potential for other immunotherapeutic approaches. These include inhibitors of additional immune checkpoints, adoptive cell transfer (ACT), and therapeutic vaccines. Patients with advanced cancers who previously had limited treatment options available may now benefit from immunotherapies that can offer durable responses and improved survival outcomes. However, despite this, a significant proportion of patients fail to respond to immunotherapy, especially those with less immunoresponsive cancer types, and there remains a need for new treatment strategies. The virtual Immunotherapy Bridge (December 1st–2nd, 2021), organized by the Fondazione Melanoma Onlus, Naples, Italy in collaboration with the Society for Immunotherapy of Cancer addressed several areas of current research in immunotherapy, including lessons learned from cell therapies, drivers of immune response, and trends in immunotherapy across different cancers, and these are summarised here.